Effectiveness of the Sustainable Fashion E-Module in Improving Students Analysis of the Fashion Industrys Environmental Impact at Vocational High School - Zulaekah, Dewi; Kusumastuti, Adhi; Widjanarko, Dwi; Wahyuningsih, Sri Endah (Journal of Vocational and Career Education, 2025)
Most students in the fashion program, particularly at SMK Negeri 6 Semarang, still show low levels of understanding regarding the principles of sustainability in the fashion industry. This is evident from the failure to meet the Learning Objective Achievement Criteria (KKTP) of 75. This condition indicates the need for more engaging, contextual, and relevant learning solutions aligned with global issues. So far, the material has been delivered conventionally through textbooks and presentations, which have proven ineffective. There is a need for the development of more engaging learning media. This study aims to assess the effectiveness of the Sustainable Fashion E-Module in enhancing student ability to analyze the fashion industries impact on the environment. The research uses a quantitative method with a pretest-posttest control group design. The sample consists of 69 students from the fashion program at SMK Negeri 6 Semarang, divided into experimental and control groups. The instruments used were pretest and posttest questions. The research data were tested for normality and homogeneity as prerequisites for analysis. Data analysis was then performed using the Normalized Gain (N-Gain) test to measure learning improvement and the Independent Sample T-Test to examine significant differences between groups. The results showed that the average N-Gain for the experimental group was 76%, categorized as effective, while the control group had only a 37% N-Gain, categorized as less effective. The T-Test showed a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. Based on these findings, it can be concluded that the use of the E-Module is effective in enhancing student cognitive abilities regarding the concept of sustainable fashion